Nuanced Reporting of Fistulas in Laryngectomy Studies. (August 2018) - Langerman, Alexander; Mitchell, Margaret
Pharyngocutaneous fistula is an important complication of laryngectomy and can vary significantly in severity. Many authors have advocated for the use of vascularized flaps (eg, pectoralis major) to reduce the risk of fistula. Prevention of small, self-limited fistulas may not be worth the morbidity of a vascularized flap in some cases. More nuanced analysis of fistula outcomes, stratified by severity, may enable better surgeon-patient decision making regarding the use of vascularized flaps in laryngectomy.